Temporal utopianism and global information networks - White, Andrew (Open Humanities Press, 2012)
In the late nineteenth century western circumnavigation of the globe and ever more accurate cartography shifted the utopian genre from the spatial to the temporal – humans’ mastery of place and space developed in contradistinction to their inability to control time, a phenomena that has become seemingly more pronounced in our modern networked societies. But does this increasing temporal instability contain utopian possibilities as well as dystopian threat? This paper engages with ideas in contemporary sociology on the nature of time to identify its potential for utopian thinking and asks whether this can be realised through global information networks.